Enhancing Textile Industry’s Employee Satisfaction through Market Sensing Capability and Internal Marketing Practice - Rizqi Wahyudi; Muhammad Iqbal; Sunarti Sunarti (Bina Teknika, 2021)
Recognize the importance of employee satisfaction in any organization, this study is piloted to forestall the effect of Internal Marketing Practice and Market Sensing capability on employees’ satisfaction in the context of the Indonesian textile industry as one of the fast-growing industry criteria in Asian markets. The drive behind this study is to examine the relationship between Internal marketing practice, Market Sensing Capability, and Employee Satisfaction. Furthermore, this study plans to see that how Cultural congruence moderates the relationship between Employee Satisfaction through Internal Marketing Practice along with Market Sensing Capability by advancing a research model. According to this study’s requirement, the quantitative methodology is chosen, with purposive method of 323 employees was selected and analyzed.  By using a web-based survey approach was selected for data, entailing of structured questionnaire. A structural equation model was operated for results on AMOS that supported the hypothetical relationship between all hypotheses. This study will guide the managers of textile firms to recognize that how important is employee satisfaction and how they can improve their practices to strengthen employee satisfaction. This study also contributes in cultural Congruence and market sensing capability literature. It is not free from limitations specifically in terms of sample size and variables that can be addressed in the future.